Relationship between Reading Interest and Indonesian Language Learning Outcomes of Elementary School Students - Agustin, Adelia Agustin; Suprapti, Suprapti (UIN Raden Mas Said Surakarta, 2024)
Students' reading interest is one of the important factors that can influence learning outcomes, especially in Indonesian language subjects, which play a role in developing students' literacy skills. This study aims to determine reading interest and Indonesian language learning outcomes and the relationship between the two variables in grade V students of MIM PK Blimbing Gatak Sukoharjo in the 2023/2024 Academic Year. This quantitative correlational study involved a class V population and a sample size of 31 students. The sampling technique used simple random sampling. The instruments used were tests and questionnaires. The data analysis technique used in this study was hypothesis testing using the product moment correlation formula. The results showed that reading interest was in the moderate category of 42% of 31 students; Indonesian language learning outcomes were also in the moderate category of 42% of 31 students. Based on the calculation of the hypothesis test, the value of sig. was obtained. 0.000 <0.05 shows a significant positive relationship between reading interest and Indonesian language learning outcomes.